Design and stigma: the relation between mobility aid and stigmatization of older people (PerCursos, 2023)
Walking aids are part of the material culture of older adults. If, on the one hand, they bring security to this population, on the other, they trigger a stigmatization process that generates negative emotions. This research reflects on the power of design and its ability to stigmatize aging through product categories (canes, crutches, and walkers). The discussion is divided into three parts: I) Things and their meanings, II) The biomedical device and III) The stigma of design. In this way, we present how design knowledge is organized by the biomedical device (medical-hospital aesthetics) and how it stigmatizes mobility aids and the aged body. Finally, from an interdisciplinary perspective, this article has contributed to understanding the stigmatization process through the meanings attributed to materiality (product-body-prejudice-emotions-product).
Keywords: mobility aids; biopolitics; prejudice; stigma; aging